2014
DOI: 10.1007/s10549-014-2979-6
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of triple-negative breast cancer metastasis by pan-DAC inhibitor panobinostat via inhibition of ZEB family of EMT master regulators

Abstract: Triple-negative breast cancer (TNBC) is a highly aggressive breast cancer subtype that lacks effective targeted therapies. The epithelial-to-mesenchymal transition (EMT) is a key contributor in the metastatic process. We previously showed the pan-deacetylase inhibitor LBH589 induces CDH1 expression in TNBC cells, suggesting regulation of EMT. The purpose of this study was to examine the effects of LBH589 on the metastatic qualities of TNBC cells and the role of EMT in this process. A panel of breast cancer cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
74
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 49 publications
7
74
0
Order By: Relevance
“…In a recent study it has been tested whether panobinostat has the ability to inhibit the migration, invasion, and metastasis of MDA-MB-231 and BT-549 cell lines, by suppressing EMT (110). In TNBC cells, panobinostat has been reported to inhibit the expression of genes associated to EMT and to induce the expression of CDH1, while these results were not found in luminal A or basal BC cell lines (106).…”
Section: Hdac Inhibitors As Anti-cancer Agentsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent study it has been tested whether panobinostat has the ability to inhibit the migration, invasion, and metastasis of MDA-MB-231 and BT-549 cell lines, by suppressing EMT (110). In TNBC cells, panobinostat has been reported to inhibit the expression of genes associated to EMT and to induce the expression of CDH1, while these results were not found in luminal A or basal BC cell lines (106).…”
Section: Hdac Inhibitors As Anti-cancer Agentsmentioning
confidence: 99%
“…Furthermore, Rhodes et al compared panobinostat to other HDAC inhibitors (SAHA, TMP269) and found that panobinostat has much more potent anti-EMT effects than the other inhibitors (110). In vitro research showed that changes in EMT-related gene expression were associated with the suppression of cell migration and invasion.…”
Section: Hdac Inhibitors As Anti-cancer Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells that have undergone an EMT exhibit enhanced cellular migration, invasion, and survival, which are required for tumor cell dissemination and metastasis formation. In many preclinical models, suppression or reversal of EMT impairs metastatic potential of many tumor cell types (8,9).…”
Section: Introductionmentioning
confidence: 99%